Investigation and Identification of Fungal Diseases of Aloe barbadensis in China - Guohui Zhang; Qingjia Wan; Xiangyang Li; Jie Deng (Biology)
The Aloe barbadensis industry plays an important role in the economic development of Yuanjiang county of Yuxi city in Yunnan province, China. In order to reduce the harm of diseases and ensure the quality of products, the occurrence of A. barbadensis was investigated. The pathogenic fungi of wild and cultivated species of A. barbadensis were isolated by a tissue separation method, and DNA sequencing was carried out by using the sequence analysis of the ribosomal rDNA-ITS region, and the pathogenic fungi were classified and identified by finally combining morphological observations. The results showed that the main fungal diseases were root rot and leaf rot disease caused by Fusarium oxysporum, leaf spot disease caused by Curvularia lunata, anthracnose caused by Colletotrichum boninense, and brown spot disease caused by Alternaria alternata on A. barbadensis.